Investigation on the Thermodynamic analysis, preparation and characterization of LaNi5 Alloy by Magnesiothermic Reduction Diffusion process - Berchmans, John Lawrence; G, Giresan; S, Raman Sankaranarayanan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The present investigation focuses on the preparation of LaNi5 intermetallic compound by “Metallothermic reduction diffusion process”. Experiments were carried out using oxides and chlorides of La and Ni metal powders as the raw materials. Granular Mg powder was used as the reductant. The thermal reduction process was carried out at 900ºC for 9 hrs in Ar atmosphere. After the completion of reaction, the contents were purified by treating with dilute acetic acid followed by de-ionized water. Thermodynamic feasibility studies were carried out to determine the probabilistic nature of formation of the desired compound. Thermal analysis was carried out to find the dissociation and decomposition temperature of the reactants. The phase purity and the elemental composition of the alloy were assessed by XRD and EDAX analyses. The morphological features of the prepared powders were examined by SEM. From this study, it has been concluded that LaNi5 alloy can be prepared with an appreciable purity by the Metallothermic reduction diffusion process.